Ребяяят, решииите пожалуйста!)) Упростите выражение а) За(а+1)+(а+2)(а-3) б)(у-3)(5-у)-(4-у)(у+6)

2

Ответы и объяснения

Лучший Ответ!
2012-04-27T09:28:54+04:00

За(а+1)+(а+2)(а-3)=3a^2+3+a^2-3a+2a-6=4a^2-a-3

(у-3)(5-у)-(4-у)(у+6)=5y-15-y^2+3y-4y-24+y^2+6y=10y-39

2012-04-27T09:30:13+04:00

3a(a+1) + (a+2)(a-3) = (3a2+3a) +(a2-3a+2a-6) = 4a2 + 2a – 6

Приравниваем к нулю:

4a2 + 2a – 6 = 0

D = b2-4ac= 22 -4*4*(-6)=100

a1=-1+5/4=1  

a2= -1-5/4 = -1,5   

4a2 + 2a – 6 = 4(a – 1)(a+1,5) = (a - 1)(4a+6)